Marginalized by Social Inequalities in Two Mainstream Primary Schools in Postcolonial Guyana (Global Journal of Human-Social Science, 2023)
This paper further extends the discourse on the social and cultural experiences of children with Special Education Needs and or Disabilities SEND in two mainstream primary schools in postcolonial Guyana The discussion in the paper extends the argument into the learning and socializing experiences and opportunities of children with SEND This study was conducted using an ethnographic approach over two semesters employing participant observation focus group discussions and unstructured interviews
Keywords: race; ethnicity; children with send; marginalization; discrimination; social inequalities